Somatic genome architecture and molecular evolution are decoupled in "young" linage-specific gene families in ciliates. - Xyrus X Maurer-Alcalá; Auden Cote-L'Heureux; Sergei L Kosakovsky Pond; Laura A Katz (PLoS ONE)
The evolution of lineage-specific gene families remains poorly studied across the eukaryotic tree of life, with most analyses focusing on the recent evolution of de novo genes in model species. Here we explore the origins of lineage-specific genes in ciliates, a ~1 billion year old clade of microeukaryotes that are defined by their division of somatic and germline functions into distinct nuclei. Previous analyses on conserved gene families have shown the effect of ciliates' unusual genome architecture on gene family evolution: extensive genome processing-the generation of thousands of gene-sized somatic chromosomes from canonical germline chromosomes-is associated with larger and more diverse gene families. To further study the relationship between ciliate genome architecture and gene family evolution, we analyzed lineage specific gene families from a set of 46 transcriptomes and 12 genomes representing x species from eight ciliate classes. We assess how the evolution lineage-specific gene families occurs among four groups of ciliates: extensive fragmenters with gene-size somatic chromosomes, non-extensive fragmenters with "large'' multi-gene somatic chromosomes, Heterotrichea with highly polyploid somatic genomes and Karyorelictea with 'paradiploid' somatic genomes. Our analyses demonstrate that: 1) most lineage-specific gene families are found at shallow taxonomic scales; 2) extensive genome processing (i.e., gene unscrambling) during development likely influences the size and number of young lineage-specific gene families; and 3) the influence of somatic genome architecture on molecular evolution is increasingly apparent in older gene families. Altogether, these data highlight the influences of genome architecture on the evolution of lineage-specific gene families in eukaryotes.